HGG-43. SUSTAINED RESPONSE OF THREE PEDIATRIC BRAFV600E MUTATED HIGH-GRADE GLIOMAS WITH BRAF AND MEK INHIBITOR THERAPY. Issue 2 (22nd June 2018) - Toll, Stephanie; Cotter, Jennifer; Judkins, Alexander; Tamrazi, Benita; Biegel, Jaclyn; Patel, Palak; Tran, Hung N; Cooper, Robert; Margol, Ashley S
Abstract: BACKGROUND: Treating high-grade gliomas in pediatric patients involves multimodal therapy with significant long-term sequelae. Despite this approach, these tumors have a high rate of recurrence. Genetic testing has allowed for targeted therapies to be investigated in tumors with BRAF V600E mutations. While BRAF inhibitors have improved survival among patients with BRAF V600E mutated melanoma, resistance develops quickly leading to trials combining BRAF and MEK inhibitors. The efficacy and side effect profile of this combination has yet to be determined in pediatric high-grade glioma patients. CASES: We describe three cases: a 12 year-old female with a high-grade glioma, a 13 year-old male with an astroblastoma and a 6 year-old female with an anaplastic ganglioglioma. All tumors demonstrated a BRAF V600E mutation, and each patient received combined dabrafenib and trametinib therapy. The 12 year-old patient experienced a significant partial response and remains progression-free after a year of combination therapy. The 13 year-old remains disease free post radiation on combination therapy for 8 months. The final patient received combination targeted therapy upfront and after significant tumor response at 3 months, remains progression-free at 1 year. All patients were strictly monitored for side effects and remain free of complications. CONCLUSIONS: To our knowledge, this is the first report of sustained responses in pediatric patients with high-grade gliomas following combined BRAF and MEK inhibitor therapy. These responses highlight the potential use of these targeted agents in this population and suggest that targeted combination therapy is a well-tolerated option in pediatric patients with documented BRAF V600E mutated high-grade gliomas.